Making pions with laser light. (4th July 2018) - Schumaker, W; Liang, T; Clarke, R; Cole, J M; Grittani, G; Kuschel, S; Mangles, S P D; Najmudin, Z; Poder, K; Sarri, G; Symes, D; Thomas, A G R; et al.
Abstract: The interaction of high intensity short pulse laser beams with plasmas can accelerate electrons to energies in excess of a GeV. These electron beams can subsequently be used to generate short-lived particles such as positrons, muons, and pions. In recent experiments, we have made the first measurements of pion production using 'all optical' methods. In particular, we have demonstrated that the interaction of bremsstrahlung generated by laser driven electron beams with aluminum atoms can produce the long lived isotope of magnesium ( 27 Mg) which is a signature for pion ( π + ) production and subsequent muon decay. Using a 300 TW laser pulse, we have measured the generation of 150 ± 50 pions per shot. We also show that the energetic electron beam is a source of an intense, highly directional neutron beam resulting from ( γ, n ) reactions which contributes to the 27 Mg measurement as background via the ( n, p ) process.